2021
DOI: 10.47391/jpma.1306
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of child health in pastoral communities in the Karakoram and Hindukush mountains, Pakistan

Abstract: Pastoralism is practiced in remote parts of the Karakoram and Hindukush high mountains, which sprawl across Northern Pakistan, with women and children travelling to high pastures with their animals during summer. There is no road access; glaciers and hazardous terrain accentuate their remoteness. This was a cross-sectional observational study, carried out along Pakistan’s border with Afghanistan’s Wakhan province. A questionnaire was used to collect basic health data. Height / length, and weight were also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a study conducted in pastoral communities along the Wakkhan Corridor in the Karakoram and Pamir mountains, results showed that 17% children were underweight and 14.2% severely underweight; 28.5% were stunted and 34.2% severely stunted. 1 Pakistan used to be self-sufficient in some basic food items, including wheat, rice, sugarcane, and milk. However, this is no longer true; Pakistan does not produce sufficient wheat, a staple in the diet of Pakistani households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in pastoral communities along the Wakkhan Corridor in the Karakoram and Pamir mountains, results showed that 17% children were underweight and 14.2% severely underweight; 28.5% were stunted and 34.2% severely stunted. 1 Pakistan used to be self-sufficient in some basic food items, including wheat, rice, sugarcane, and milk. However, this is no longer true; Pakistan does not produce sufficient wheat, a staple in the diet of Pakistani households.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is common in mountain communities, and mortality from pneumonia is common. [1][2][3] Malnutrition amongst children in Pakistan is common, with stunting in 38% and severe stunting in 17%; 23% children are underweight and 8% are severely underweight. 4 Causes of malnutrition are manifold, including low birth weight, poor feeding (lack of or insufficient breast feeding and complimentary feeding), lack of maternal education, large family size, lack of vaccinations, poverty, poor sanitation, and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…To explain this, the nutritional intervention adopted in this study covers a series of measures, all of them could improve the guardians’ cognition of scientific infant feeding, make them aware of the impact of poor feeding methods on the growth and development of infants, and improve their attention to scientific infant feeding. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…It could be known from the results of this study that (1): in terms of gross motor, fine motor, language and individual society, the score of the observation group was higher than that of the control group after To explain this, the nutritional intervention adopted in this study covers a series of measures, all of them could improve the guardians' cognition of scientific infant feeding, make them aware of the impact of poor feeding methods on the growth and development of infants, and improve their attention to scientific infant feeding. 8,9 At the same time, one-to-one consultation was conducted once a week to clarify the specific feeding situation of infants in detail and provided timely scientific guidance to guardians on scientific feeding, which had a positive impact on improving the standardization of scientific feeding of infants and ensuring their daily nutritional intake. 10,11 Furthermore, appropriate emotional interventions were also given to the guardians to avoid excessive fear and other negative emotions, this measure played a crucial role in improving the intimacy between guardians and infants and promoting the development of the physical and mental health of infants.…”
Section: Discussionmentioning
confidence: 99%